2017
DOI: 10.1038/am.2017.187
|View full text |Cite
|
Sign up to set email alerts
|

A novel ultra-thin-walled ZnO microtube cavity supporting multiple optical modes for bluish-violet photoluminescence, low-threshold ultraviolet lasing and microfluidic photodegradation

Abstract: ZnO optical microcavities have shown great promise as a potential core component material/structure for ultraviolet lasers, lightemitting diodes and photonic sensors because of their outstanding optoelectronic properties. Here, we report a novel ultra-thinwalled ZnO (UTW-ZnO) microtube cavity with a wall thickness of~750 nm, supporting multiple types of optical modes, including in-tube Fabry-Perot modes, in-wall Fabry-Perot modes and wave-guided whispering gallery modes (WG-WGMs). The free-exciton recombinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 41 publications
1
17
0
2
Order By: Relevance
“…In this paper, the evolution and quality of the resonant peaks in relation to the size and shape of the resonant cavity and to the reflectance efficiency of the facets are described. It was shown that doing measurements that mapped the evolution of the optical resonant modes along the length of the structure will helped to identify the regions with resonant cavities that had better performance for applications such as lasing [2,3,13,14], sensors [12], immunosensors [15], or optical filters [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the evolution and quality of the resonant peaks in relation to the size and shape of the resonant cavity and to the reflectance efficiency of the facets are described. It was shown that doing measurements that mapped the evolution of the optical resonant modes along the length of the structure will helped to identify the regions with resonant cavities that had better performance for applications such as lasing [2,3,13,14], sensors [12], immunosensors [15], or optical filters [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work has confirmed V Zn acting as stable recombination centers up to 773 K (Wang et al, 2016(Wang et al, , 2017a. Figure 3E shows the temperature-dependent PL spectra of a 15%-O 2 HC-ZnO microrod measured by a CW 325-nm-line He-Cd laser with the polarization perpendicular to the c-axis.…”
Section: Mechanism Of Current-induced Thermal Tunneling El From Hc-zno Microrodsmentioning
confidence: 81%
“…Figure 1A shows the setup for growth of HC-ZnO microrods with massive V Zn -related acceptors and Vorelated donors, as proposed in our previous studies (Hu et al, 2018b;Wang et al, 2016Wang et al, , 2017aWang et al, , 2017b. To efficiently control the V O concentration, the O 2 /Ar mixed carrier gas with variable oxygen pressure ratios (i.e., 15%, 20%, and 25%) was used during OVSP growth; a mixture of ZnO and graphite powders with a definite weight ratio of 2:1 was pressed as the reactive green body rod.…”
Section: Fabrication and Characterization Of Hc-zno Microrodsmentioning
confidence: 99%
See 2 more Smart Citations